An epidemiological review of changes in meningococcal biology during the last 100 years. (October 2013) - Abio, Anne; Neal, Keith R.; Beck, Charles R.
<x content-type="archive" xml:space="preserve">Abstract</x> Aim: The aim of this study was to assess changes in trends of meningococcal disease and strain diversity of Neisseria meningitidis in Europe, South America, and Africa over the last 100 years. Methods: Healthcare databases and sources of grey literature were searched in 2012 and records were screened against the protocol eligibility criteria using a three-stage sifting process. Studies included in the review were subject to data extraction. Results were summarised using a narrative approach. Results: Serogroup A was the dominant cause of invasive meningococcal disease in Europe before and during World Wars I and II. Whilst serogroup B has been dominant from the 1970s in Europe and the 1980s in South America, outbreaks have emerged associated with serogroups W135 and Y in the twenty-first century. There has been a shift in the age groups affected by invasive meningococcal disease with an increase in incidence among the elderly associated with serogroup Y and a decline in serogroup C among adolescent populations. Recent outbreaks of serogroup W135 have occurred in some countries in South America. The epidemiological trend of invasive meningococcal disease has remained largely static across Africa and dominated by serogroup A although recently serogroups X and W135 have accounted for a large proportion of morbidity and mortality. Conclusion: The epidemiology of N. meningitidis has been dynamic in Europe and South America especially over the last 30 years. Routine vaccination with serogroup C vaccines has led to reduced carriage and incidence of invasive meningococcal disease and herd immunity.